Prognostic role of FDG PET/CT in patients with differentiated thyroid cancer treated with 131-iodine empiric therapy. Issue 42 (October 2017) - Salvatore, Barbara; Klain, Michele; Nicolai, Emanuele; D'Amico, Domenico; De Matteis, Gianluca; Raddi, Marco; Fonti, Rosa; Pellegrino, Teresa; Storto, Giovanni; Cuocolo, Alberto; Pace, Leonardo
Abstract: Background: To assess the long-term prognostic value of 18 F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) in patients with differentiated thyroid carcinoma (DTC) undergoing empiric radioiodine (RAI) therapy due to raising values of thyroglobulin (Tg). Methods: Forty-nine patients with histological diagnosis of DTC (31 with papillary and 18 with follicular carcinoma) follow-up for a mean period of 7.9 ± 5 years after empiric RAI therapy were retrospectively analyzed. Results: FDG-PET/CT was negative in 15 (30.6%) patients and positive in 34 (69.4%), whereas postradioiodine therapy whole body scan (t-WBS) was negative in 16 (32.7%) and positive in 33 (67.3%) patients. FDG-PET/CT and t-WBS were in agreement in 32 patients (7 both negative and 25 both positive); on the contrary, in 17 patients there was disagreement between FDG-PET/CT and t-WBS ( P = ns). At short-term follow-up, Tg normalized in 19 (38.8%) patients and was unchanged or increased in 30 (61.2%). Of the 15 patients with negative FDG-PET/CT, 11 (73.3%) showed Tg normalization, whereas of the 34 patients with positive FDG-PET/CT, only 8 (23.5%) had Tg normalization (χ 2 =8.9, P < .005). At multivariate analysis, FDG-PET/CT and Tg normalization at short-term follow-up were independent predictors of disease-free survival (χ 2 =26.3, P < .0001), while Tg normalization was the only variable associated with overall survival χ 2 =7.2, P < .01). Conclusion: FDG-PET/CT in association with Tg normalization at short-term follow-up may be useful for long-term prognostic stratification in DTC patients.